Pelatihan Desain Konten Islami Visual Sebagai Sarana Ekspresi Digital di Era Society 5.0 Bagi Remaja Yayasan Kopia Raya Insani - Hani Harafani (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the readiness of the younger generation in facing career challenges in the era of technological disruption through the optimization of digital skills. This activity is carried out in the environment of the Foundation under the name of the Kopia Raya Insani Foundation which will focus on three important pillars of community life, namely: Religion, education, and social and humanity. Islamic visual content design training is becoming increasingly relevant in the era of Society 5.0, where digital expression plays an important role in the dissemination of values ​​and identities. In addition, this training is also intended to empower individuals in creating Islamic visual content that is attractive, informative, and in accordance with technological developments. This training equips participants with basic knowledge of design, principles of Islamic aesthetics, and the use of various digital platforms to spread messages of goodness. Through a practical and applicable approach, participants are expected to be able to produce visual design works that not only enrich the treasury of Islamic content in cyberspace, but also become an effective means for preaching and interacting positively in the digital community. This training is expected to increase Islamic visual literacy and encourage active participation in realizing a digital society that is noble and has an Islamic perspective.